SISTEM INFORMASI MANAJEMEN, SISTEM PELAYANAN, GAYA KEPEMIMPINAN SERTA PENGARUHNYA TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN KEBOMAS GRESIK - Romadhan, Achmad; Sudarsono, Heri; jondar, aloysius (JEB17 : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of management information systems, service systems, and leadership styles on employee performance at the Kebomas District Office in Gresik. In the era of digitalization and increasing public service demands, optimizing the performance of government officials is crucial. This research employs a quantitative approach using a survey method, with questionnaires as the primary instrument. The data were analyzed using multiple regression analysis to determine both the simultaneous and partial effects of each independent variable on employee performance. The results indicate that all three independent variables significantly influence performance, with the management information system being the dominant factor. The implications of this study highlight the importance of developing information systems and participative leadership styles to improve the quality of public services. Keywords: management information system, service system, leadership style, employee performance, public service.